A study on inventory system in UiTM Shah Alam (main campus) / Nor Khalilah Rosli - Rosli, Nor Khalilah (Faculty of Architecture, Planning and Surveying, 2009)
Inventory is a way to control and manage equipment or items in the company. It is a highly important role in business. The word of inventory means a hold list of items. This term can be used everywhere and it refer to the list of stock and also to stock itself. The purpose of this study done at Universiti Teknologi MARA campus Shah Alam is to know the way of inventory being managed in the institution. It also explains about the importance of having the inventory to UiTM party and then gives a conclusion on the inventory management and controlled in the UiTM.